KLASIFIKASI PENYAKIT PENGOROK TANAMAN DAUN PADA TANAMAN MANGGIS MENGGUNAKAN METODE GRAY LEVEL CO-OCCURRENCE MATRIX DAN SUPPORT VECTOR MACHINE - Ramadhani Sheffi Tiara Gultom (2020)
Indonesia is a country that relies on the agricultural sector to help the country's economy. According to ministry of agriculture dara from 2018, mangosteen plant is one of main export commodity from Indonesia. All parts of mangosteen plant has plenty of benefit and good for health. However, borers pest can be a threat to mangosteen cultivator. This pest damaged mangosteen leaf and drop the leaf quality so that its hard to be exported and to be consumed. This pest can be seen by the naked eye where its characteristics are porous shape and brown colored leaf that is caused by borers pest which is transplanted in mangosteen leaf. This image processing research are used for detecting borers pest on mangosteen leaf with Gray Level Co-occurrence matrix and colour moments and classified with Support Vector Machine.